How do topics and emotions develop in elementary school children? A text mining perspective based on free-writing text over 6 years - Liu, Mengjun; Jiang, Xinyu; Zhang, Bingbing; Song, Ting; Yu, Gang; Liu, Guofang; Jiang, Nan; Wu, Di; Zhou, Zhi (Frontiers in Psychology, 2023)
Text Mining brings new perspectives and great potential for investigating environmental influences and emotional expression in children’s development. Using 4,556 free-text writing data from grade 1 to grade 6, through topic modeling and sentiment analysis in text mining, this paper reveals the different topics and concern trends of children during the six years of elementary school and the differences in sentiment expression under different topics. The results show the following: (1) Children prefer to focus on the topics of school and family in elementary school; (2) With the growth of grades, the proportion of family topics continues to decline, while that of social culture topics keeps rising; (3) When describing school, family, social culture, and interest, children mostly express negative emotions, and when describing peers and ability they mostly express positive emotions; (4) As the grade increases, the emotional expression on social culture topics become negative, while that on ability and interest topics become positive, and there are more differences in emotion expression between topics in junior and senior elementary grades.